Dynamics of Asymmetric Decentralization on the Implementation of Regional Autonomy in Aceh - Wais Alqarni; Muhammad Suhail Ghifari; Yuspani Asemki; Muhammad Rizki; Bela Safira; Isti Nindiah; Melida Rosa; Nuzulul Rahmi; Restu Fadhil; Wahyuni Wahyuni (Universitas Muhammadiyah Yogyakarta, 2022)
Decentralization is a global trend whose presence is believed to be able to overcome various problems in modern and unitary countries. The concept of asymmetry developed from the concept of asymmetric federation which was introduced by Charles Tarlton in 1965. Asymmetric decentralization is not an ordinary delegation of authority in the form of transfers, but in the form of special powers that are only given to certain regions. Aceh is one of the provinces that received or bears the status of a special autonomous region because it is seen from the journey that the province of Aceh has gone through as well as considerations from the history, socio-culture of its people and politics. Aceh's status as a special autonomous region may not work as expected if the central government and the Aceh provincial government do not carry out optimally in accordance with the mandate of Law no. 11 of 2006 concerning the Government of Aceh was implemented. A truly optimal implementation is needed so that it will produce what is expected. This research method is carried out by means of a literature study with strong and accountable references